2011
DOI: 10.1097/pas.0b013e31821a5692
|View full text |Cite
|
Sign up to set email alerts
|

How to Define a Positive Circumferential Resection Margin in T3 Adenocarcinoma of the Esophagus

Abstract: A positive circumferential resection margin (CRM) is associated with poor survival after esophagectomy for cancer. The Royal College of Pathologists (RCP) defines a CRM when tumor is found <1 mm of the lateral margin whereas the College of American Pathologists (CAP) defines CRM when tumor cells are located at the lateral margin. This study evaluates the clinical prognostic significance of CRM on overall survival (OS) and disease-free survival (DFS) in patients who underwent esophagectomy for T3 esophageal ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 21 publications
3
67
2
Order By: Relevance
“…Interestingly, another study was only able to demonstrate a negative effect on overall survival in ESCC for CRM positive patients when judged by CAP 199 criteria (HR 5.26; 95% CI 2.37-11.32; p < 0.001) and not RCP criteria (HR 1.3; 95% CI 0.62-2.98; p = 0.50) in multivariate analysis [18]. Similar results were found in 3 other studies were CAP criteria yielded a significant prognostic influence on overall survival while RCP criteria did not [12,13,19]. Notably, some studies were not able to show an effect of the CRM status on overall survival [15,[20][21][22][23].…”
Section: Survivalsupporting
confidence: 78%
See 3 more Smart Citations
“…Interestingly, another study was only able to demonstrate a negative effect on overall survival in ESCC for CRM positive patients when judged by CAP 199 criteria (HR 5.26; 95% CI 2.37-11.32; p < 0.001) and not RCP criteria (HR 1.3; 95% CI 0.62-2.98; p = 0.50) in multivariate analysis [18]. Similar results were found in 3 other studies were CAP criteria yielded a significant prognostic influence on overall survival while RCP criteria did not [12,13,19]. Notably, some studies were not able to show an effect of the CRM status on overall survival [15,[20][21][22][23].…”
Section: Survivalsupporting
confidence: 78%
“…In the first study of CRM involvement by Sagar et al [25], significantly (p < 0.01) more patients with a positive CRM (55%) developed a local recurrence as compared to those without involvement of the CRM (13%) [25]. These results were later proven by other studies, which also identified a prognostic role of a positive CRM on recurrences [3,13,14,17,18,22,26]. Chao et al [26] found a significant influence of an involved CRM not only on loco-regional but also on distant recurrences, while an involvement to the CRM of less than 1 mm was associated with early loco-regional recurrences.…”
Section: Recurrencesupporting
confidence: 73%
See 2 more Smart Citations
“…The College of American Pathologists (CAP) defines a positive CRM as tumour at the cut margin (TAM), which has been advocated in some studies4, 5, 6, 7, 8, 9, whereas the Royal College of Pathologists (RCP) defines a positive CRM as tumour within 1 mm, preferred in other studies10, 11, 12, 13. Some studies have found the CRM to be independently prognostically significant4 7, 9 10, 13, 14, 15, 16, and others have not5 6, 11 12, 17, 18, 19. A positive margin may increase the likelihood of locoregional and systemic tumour recurrence9 20, although it is unclear whether the latter is simply a reflection of a larger, more advanced tumour.…”
Section: Introductionmentioning
confidence: 99%